The role of stromal cancer-associated fibroblasts in pancreatic cancer - Dagny von Ahrens; Tushar D. Bhagat; Deepak Nagrath; Anirban Maitra; Amit Verma (Journal of Hematology & Oncology, 2017)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a lethal cancer generally refractory to conventional treatments. Cancer-associated fibroblasts (CAFs) are cellular components of the desmoplastic stroma characteristic to the tumor that contributes to this treatment resistance. Various markers for CAFs have been explored including palladin and CD146 that have prognostic and functional roles in the pathobiology of PDAC. Mechanisms of CAF-tumor cell interaction have been described including exosomal transfer and paracrine signaling mediated by cytokines such as GM-CSF and IL-6. The role of downstream signaling pathways including JAK/STAT, mTOR, sonic hedge hog (SHH), and NFkB have also been shown to play an important function in PDAC-CAF cross talk. The role of autophagy and other metabolic effects on each cell type within the tumor have also been proposed to play roles in facilitating CAF secretory function and enhancing tumor growth in a low-glucose microenvironment. Targeting the stroma has gained interest with multiple preclinical and clinical trials targeting SHH, JAK2, and methods of either exploiting the secretory capability of CAFs to enhance drug delivery or inhibiting it to prevent its influence on cancer cell chemoresistance. This review summarizes the most recent progress made in understanding stromal formation; its contribution to tumor proliferation, invasion, and metastasis; its role in chemoresistance; and potential therapeutic strategies on the horizon.